Ενεργειακή αξιολόγηση ψυγείου οικιακής χρήσης - Καραγιάννης, Μιχάλης (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2013)
The objective of this dissertation is to study and evaluate the energy performance of domestic refrigerators. More specifically, the increase in efficiency of domestic refrigerators is investigated, ultimately aiming to save on electricity consumption. There is also a description of methods with which refrigerators may achieve higher efficiencies with reference to existing studies and their results. After analysing the above, there is an extensive description of the factors which influence the energy consumption of a domestic refrigerator and the various ways that may be adopted by the consumers to save energy are outlined. The reliability and the precision of temperature control units and other devices is examined through laboratory testing, along with the question whether there is an increase of electricity consumption by reducing the internal temperature. Furthermore, the differences between the mechanical and electronic temperature control units are observed and a study follows on the potential to reduce a refrigerator’s electricity consumption using power factor correction. Finally, there is a consideration about whether the increase and decrease of the amount of refrigerant in the system as well as other modifications of the refrigeration cycle affect the refrigerator’s performance.
Keywords: Domestic Refrigerator; Evaluate The Energy Performance; Save On Electricity Consumption; Refrigeration Cycle; Ψυγεία Οικιακής Χρήσης; Ενεργειακή Αξιολόγηση; Εξοικονόμηση Ηλεκτρικού Ρεύματος; Ψυκτικό Κύκλωμα